BREVE HISTORIA DEL DERECHO PENAL COLOMBIANO (2016)
Want the author with this brief text, not exhaustive thus show in key short an overview of the development that has taken our Colombian Criminal Law, through its republican history, showing their strengths and weaknesses, in the eagerness to implement justice criminal law in our country to punish crimes.